Effect of Cobalt Doping on the Stability of CaO‐Based Catalysts for Dimethyl Carbonate Synthesis via the Transesterification of Propylene Carbonate with Methanol. Issue 38 (8th October 2021) - Huo, Linmeng; Wang, Tian; Pu, Yanfeng; Li, Chenxin; Li, Lei; Zhai, Minglu; Qiao, Congzhen; Bai, Yan
Abstract: To improve the stability of the a CaO catalyst with high activity in the synthesis of dimethyl carbonate (DMC) at low‐temperatures via the transesterification of propylene carbonate (PC) with methanol, a series of Co‐doped CaO nanoparticles were synthesized with different cobalt contents via the sol‐gel method, and the catalytic performance of these catalysts increased in the order of 0.7Ca0.3Co<0.8Ca0.2Co<CaO<0.95Ca0.05Co<0.9Ca0.1Co. The characterization results of BET, XRD, FT‐IR, SEM, TEM, CO2 ‐TPD and XPS indicated that the addition of cobalt to CaO could form a novel layered structure of the Ca3 Co4 O9 carrier, which favoured the formation of strongly basic sites and then improved the activation of PC and methanol. The catalytic activity of traditional metal oxide catalysts is lower than that of pure CaO; however, the initial activity of the novel layered structure of the 0.9Ca0.1Co catalyst reached 72.9 %, which is obviously higher than that of 65.8 % for CaO. Furthermore, the results of long‐term catalytic evaluation showed that the best 0.9Ca0.1Co catalyst exhibited a stable PC conversion of 95.4 % and DMC yield of 93.1 % at 65 °C even after 168 h in the reactive distillation reactor. The deactivation mechanism showed that the layered structure of Ca3 Co4 O9 could stabilize CaO and prolong the life of the catalyst. Abstract : The addition of cobalt to CaO could form a novel layered structure of the Ca3 Co4 O9 carrier, which could improve the activity and stability of the CaO catalyst in the synthesis of dimethyl carbonate (DMC) via transesterification of propylene carbonate (PC) with methanol. Then, the results of long‐term catalytic evaluation showed that the best 0.9Ca0.1Co catalyst exhibited a stable PC conversion of 95.4 % and DMC yield of 93.1 % at 65 °C even after 168 h in the reactive distillation reactor.